2013
DOI: 10.1371/journal.pone.0063588
|View full text |Cite|
|
Sign up to set email alerts
|

IL-26 Promotes the Proliferation and Survival of Human Gastric Cancer Cells by Regulating the Balance of STAT1 and STAT3 Activation

Abstract: Interleukin-26 (IL-26) is one of the cytokines secreted by Th17 cells whose role in human tumors remains unknown. Here, we investigated the expression and potential role of IL-26 in human gastric cancer (GC). The expression of IL-26 and related molecules such as IL-20R1, STAT1 and STAT3 was examined by real-time PCR and immunohistochemisty. The effects of IL-26 on cell proliferation and cisplatin-induced apoptosis were analyzed by BrdU cooperation assay and PI-Annexin V co-staining, respectively. Lentiviral me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 32 publications
2
47
0
Order By: Relevance
“…Interestingly, gene annotation revealed IL26 to be the gene most upregulated (Table S2) and PDGF-A to be the gene most downregulated (Table S3) in TIML-NK cells as compared with control NK cells. As IL26 mediates both proliferative as well as anti-apoptotic effects 48 and induces T H 1 polarization, 49 it is tempting to speculate that IL26 secreted by TIML-NK cells might modulate subsequent adaptive immune responses. On the other hand, the plateletderived growth factor-A (PDGF-A) has so far not been associated with NK cell function; however, downregulation of the corresponding c-Kit / PDGF receptor on dendritic cells indeed effectively improves NK cell-triggering.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, gene annotation revealed IL26 to be the gene most upregulated (Table S2) and PDGF-A to be the gene most downregulated (Table S3) in TIML-NK cells as compared with control NK cells. As IL26 mediates both proliferative as well as anti-apoptotic effects 48 and induces T H 1 polarization, 49 it is tempting to speculate that IL26 secreted by TIML-NK cells might modulate subsequent adaptive immune responses. On the other hand, the plateletderived growth factor-A (PDGF-A) has so far not been associated with NK cell function; however, downregulation of the corresponding c-Kit / PDGF receptor on dendritic cells indeed effectively improves NK cell-triggering.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have revealed the role played by Stat3 in cell proliferation, motility and invasiveness [38][39][40]. Similarly, in vivo animal studies have highlighted the fact that Stat3 has an important role to play in gastric tumorigenesis [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Even though the current knowledge remains superficial from a wholistic point of view, there is now evidence that the effector function of IL-26 depends upon the type of cellular target and the costimulatory conditions [14,18,21]. Despite the structural similarity with the archetype anti-inflammatory cytokine IL-10, and the sharing of one of its heterodimer receptor subunits, functional studies are compatible with IL-26 driving or sustaining inflammation rather than suppressing it.…”
Section: Effector Functionsmentioning
confidence: 99%
“…In another study, IL-26 caused decreased proliferation in a colorectal-cancer cell line [11]. In human gastric-cancer cells, on the other hand, IL-26 induces STAT3-dependent upregulation of Bcl-2, Bcl-xl and c-myc malignant carcinoma cells, thereby promoting both cell survival and proliferation [21]. Thus, IL-26 exerts potentially important effects on cancer cells but the current data appear conflicting and it remains for the conceptual importance of IL-26 in cancer to be clarified.…”
Section: Cancermentioning
confidence: 99%